Profile of Patients with Brain Abscess - Khatiwada, Roshan; Bista, Prakash; Jha, Rajiv; Khadka, Nilam Kumar; Shrestha, Rajendra; Khambu, Bikesh (Birat Journal of Health Sciences, 2020)
Introduction: Despite of the advent of modern neurosurgical techniques and antibiotics, brain abscess possesses a major neurosurgical challenge in treatment. In this study we present the profile , clinical features , radiological features , treatment received and their outcome of cases of brain abscess that we managed in our center. Methods: Total 30 patients diagnosed with brain abscess who underwent treatment in last four months were included in this study. A descriptive observational data of brain abscess and the outcome variables in the form of Glasgow Outcome Scale (GOS) at discharge , hospital stay, and mortality were studied. The ultimate outcome was measured in Glasgow Outcome Score. Results: Total number of cases was 30, outwith male dominance 19 (63.3%) . Age ranged from 2 months to 60 years. Twenty-five patients were of acute pyogenic abscess while and rest were tubercular abscess. Common clinical features were headache (70%), fever (30%), vomiting (23%), seizure (23%) and focal neurological deficits (16.7%). Overall mean hospital stay was 31 days. The common aetogenic factors included chronic suppurative otitis media (16.7%), tuberculosis (16.7%), post-traumatic (10%), congenital heart disease (10%) and rest (46%) were of unknown source. lobe Temporal lobe and cerebellar were most common site involved (20%) each followed by frontal (16.7%). Surgery was done in 25 (83.3%) cases out of which 12 underwent burr hole and aspiration and 12 patients underwent craniotomy and excision and one patient underwent burr hole and followed by craniotomy. Five patients were managed conservatively. Complete resolution of abscess with complete recovery of preoperative neurological-deficit was seen n 28 (93.3%) cases. Conclusion: Early diagnosis and timely intervention improves the outcome of brain abscess. Most of the cases required surgical intervention and drainage of pus and had good postoperative outcome.